A drop of the hard stuff - Block, Lawrence, 1938- (A Matt Scudder mystery, 2012)
Matt Scudder and Jack Ellery were at school together but never exactly friends. Twenty years later, when Scudder was a detective and Jack was standing on the other side of the one-way glass in a police line-up, it was clear their lives had taken very different paths.What they shared, however, was a battle with alcohol. Now Jack is on the ninth step of the AA program and it's time to make amends to the people he's wronged over the years because of his addiction. But when he ends up shot in the head, and it's clear that stirring up the past was not such a good idea, it's up to Scudder to find the killer.